TINJAUAN SOSIOLOGIS KESEJAHTRAAN KELUARGA PETANI DI DESA MALAT, KECAMATAN GEMEH, KABUPATEN TALAUD - Enal Renady Wundu; Rasyid Umaternate; Siti Fatimah (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
The purpose of this study was to describe the sociological review of the welfare of farming families in Malat Village, Gemeh District, Talaud District. The research method that we use is qualitative research in this study. Methods of data collection researchers use in the form of interviews, observation and study of documents. While the data analysis used is in the form of data reduction, data presentation, and drawing conclusions. The result of the research is that the level of welfare from a sociological point of view for farmers in Malat village is still far from the word prosperous. from the results of the garden they already feel very grateful and also for their clothing needs they don't have to follow the model as long as they have clothes to wear, they feel enough and for their housing needs some are independent and some still live with their parents in one house on the grounds that the house they live belong to the family.